Effectiveness and safety over 3 years after the 2-year U-Act-Early trial of the strategies initiating tocilizumab and/or methotrexate. (20th December 2019) - Verhoeven, Maxime M A; Tekstra, Janneke; Welsing, Paco M J; Pethö-Schramm, Attila; Borm, Michelle E A; Bruyn, George A W; Bos, Reinhard; Griep, Ed N; Klaasen, Ruth; van Laar, Jacob M; Lafeber, Floris P J G; Bijlsma, Johannes W J; et al.
Abstract: Objectives: U-Act-Early was a 2-year, randomized placebo controlled, double-blind trial, in which DMARD-naïve early RA patients were treated to the target of sustained remission (SR). Two strategies initiating tocilizumab (TCZ), with and without methotrexate (MTX), were more effective than a strategy initiating MTX. The aim of the current study was to determine longer-term effectiveness in daily clinical practice. Methods: At the end of U-Act-Early, patients were included in a 3-year post-trial follow-up (PTFU), in which treatment was according to standard care and data were collected every 3 months during the first year and every 6 months thereafter. Primary end point was disease activity score assessing 28 joints (DAS28) over time. Mixed effects models were used to compare effectiveness between initial strategy groups, correcting for relevant confounders. Between the groups as randomized, proportions of patients were tested for DMARD use, SR and radiographic progression of joint damage. Results: Of patients starting U-Act-Early, 226/317 (71%) participated in the PTFU. Over the total 5 years, mean DAS28 was similar between groups ( P  > 0.20). During U-Act-Early, biologic DMARD use decreased in both TCZ initiation groups and increased in the MTX initiation group, but during follow-up this trend did not continue. SR was achieved at least once in 99% of patients. Of the 226 patients, only 30% had any radiographic progression over 5 years, without significant differences between the groups. Conclusion: Although in the short-term the strategies initiating TCZ yielded the most clinical benefit, in the longer-term differences in important clinical outcomes between the strategies disappeared, probably due to continuation of the treat-to-target principle.